The analysis of the relationship between economic growth and electricity consumption in South American continents: MS-Granger causality analysis - Bildirici, Melike E. (TAYLOR & FRANCIS INC, 2016)
In this study, the relationship between electricity consumption and economic growth is investigated by MS-VAR and MS-Granger Causality methods. This study involves five countries in American continents: the Dominican Republic, Ecuador, El-Salvador, Guatemala, and Nicaragua for the period 1970-2010. In sum, some evidence of bidirectional Granger causality was found between electricity consumption and economic growth.
Keywords: Electricity consumption; MS-VAR and MS-Granger Causality methods; ENERGY-CONSUMPTION; UNIT-ROOT; GNP; COUNTRIES; TESTS; Energy & Fuels